2021
DOI: 10.3389/fspor.2021.603415
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the COVID-19 Pandemic on Athletes

Abstract: This study explored the influence of athletic identity and sports participation on the psychological well-being of athletes during a pandemic. The objective of the study was to understand the psychological impact of the coronavirus lockdown measure on athletes who were not able to carry out their normal daily routine. Athletes from nine different sports completed an online survey during the sixth week of the total lockdown in Nigeria. The online survey consists of an athletic identity scale and the Kessler Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…They found that team sports’ athletes had a higher degree of identity than individual sports’ athletes. In addition, Uroh and Adewunmi [ 46 ] compared athletic identity and psychological distress between individual and team sports among Nigerian athletes during the COVID-19 lockdown. Individual sports athletes tended to have lower levels of athletic identity and higher levels of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that team sports’ athletes had a higher degree of identity than individual sports’ athletes. In addition, Uroh and Adewunmi [ 46 ] compared athletic identity and psychological distress between individual and team sports among Nigerian athletes during the COVID-19 lockdown. Individual sports athletes tended to have lower levels of athletic identity and higher levels of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individual sport athletes experience more anxiety and psychological distress than team sports athletes [ 47 ]. These studies suggest that in situations such as the COVID-19 pandemic, athletes who participate in individual sports are more likely to experience a lower degree of athletic identity and worse mental health [ 11 , 46 ]. Since the individual sport athletes had lower student-athletes’ identity than the team sport athletes, it would be possible to examine the concerns suggested in previous studies as they apply to Japanese student athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we see in the current study that Polish athletes, especially women, have a stronger response to the lockdown situation, which should receive particular interest. Numerous studies show that athletes all around the world experienced a decrease in mental wellbeing, an increased level of stress, anxiety, depressive symptoms and feelings of anger, confusion during the first lockdown, and women and individual sports representatives seem to have the highest costs of the problematic situation of pandemic [1,9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Athletes with coping strategies as cognitive reconstructive and emotional calm suffered less from negative emotional states [7]. However, when considering athletes and non-athletes, there are studies which show that athletes report greater anxiety than non-athletes, and that the level of athletic identity (the degree to which an individual identifies with the athletic role) has a tendency to decrease [8,9].This phenomenon occurs more among young athletes who may resign from sport [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is research that analyzes the psychosocial problems affecting athletes [35,[55][56][57] but few or nonexistent research that analyzes the levels of stress suffered by coaches. For this reason, this research focuses on determining the level of psychological risks and analyzing the psychosocial risks of basketball coaches in their professional development during the current 2020-2021 season characterized by the COVID-19 pandemic conditions.…”
Section: Introductionmentioning
confidence: 99%